Credit Default Swaps around the World. (24th August 2021) - Bartram, Söhnke M; Conrad, Jennifer; Lee, Jongsub; Subrahmanyam, Marti G
Abstract: We analyze the impact of the introduction of credit default swaps (CDSs) on real decision-making within the firm. Our structural model predicts that CDS introduction increases debt capacity more when uncertainty about the credit events that trigger CDS payment is lower. Using a sample of more than 56, 000 firms across 51 countries, we find that CDSs increase leverage more in legal and market environments where uncertainty about CDS obligations is reduced and when property rights are weaker. Our results highlight the importance of legal uncertainty in the interpretation of the underlying trigger events of global credit derivatives.